Comparison of Vitamin D Levels in Patients with Dengue Haemorrhagic Fever and Dengue Fever - Muhammad Rizwan Mahmud , Sadaf Zaman , Nadeem Naseem , Nadeem Iqbal , Nida Tanveer , Mohammad Ali Khalid , Haider Zaigham Baqai, Muhammad Rizwan Mahmud , Sadaf Zaman , Nadeem Naseem , Nadeem Iqbal , Nida Tanveer , Mohammad Ali Khalid , Haider Zaigham Baqai (Journal of Rawalpindi Medical College, 2018)
Background: To compare vitamin D levels in patients of dengue hemorrhagic fever with dengue fever Methods: A total of 50 patients with diagnosed dengue fever, who fulfilled the inclusion criteria were enrolled in the study. Patients were divided into two groups having 25 participants each; one group had Dengue fever (DF) while the other was suffering from dengue hemorrhagic fever (DHF). Vitamin D was estimated by the chemiluminescence method. Pearson’s Chi-square was applied to compare the proportion of patients in each study group. Relative Risk was measured along with 95% confidence interval. Significant p-value was < 0.05. Results: Mean age of patients was 37.79 ± 15.2 years (range: 16-90 years). There were 74% males and 26% females. Mean vitamin D levels in dengue fever patients were higher (21.5 ± 13.6 ng/ml) as compared to Dengue hemorrhagic fever (12.4 ± 5.6 ng/ml). The difference was statistically significant (p=0.003). Conclusions: Vitamin D may have a role in the management of dengue fever. Low levels of vitamin D might be associated with dengue hemorrhagic fever.